Economic effects of grouse-friendly forest management - Haara, Arto; Matala, Juho; Melin, Markus; Miettinen, Janne; Korhonen, Kari; Packalen, Tuula; Varjo, Jari (Suomen metsätieteellinen seura, 2021)
Traditional timber production may have negative effects on other ecosystem services. Therefore, new forest management guidelines have been developed in order to enhance a habitat suitable for wildlife. In Finland, a recent example of this is grouse-friendly forest management (GFFM) which emphasises the preservation of grouse species (Tetronidae) habitats. This study aimed to analyse the economic effects of these guidelines. An analysis was made on how the application of GFFM affected the Net Present Value (NPV) in a 30-year simulation of forest management of four large forest holdings located from south to north in Finland. In the simulations, traditional forest management practices were compared to two levels of GFFM. Five levels of interest rate were used, namely 1, 2, 3, 4, and 5%. In most of the simulations, the NPV was reduced by about 1% or less due to the application of GFFM in comparison to the traditional reference forest management. Only in one case with more intensive GFFM, was the reduction of NPV more than 5%. The interest rates had an impact on the differences between the management approaches. For example, a low interest rate resulted in a higher thinning intensity in GFFM in comparison to traditional forest management, which lead to a higher NPV in GFFM. To sum up, it seems that it would be possible to manage forest holdings in a grouse-friendly manner with minor effects on the economics.
Keywords: kanalinnut; metsän hoito; metsäekologia; riistalinnut; riista; game keeping; grouse; interest rate; simulation; trade-offs